Predictors of radiographic erosion and joint space narrowing progression in patients with early rheumatoid arthritis: a cohort study - Rydell, Emil (Arthritis Res Ther, 2021)
BACKGROUND: Radiographic damage in rheumatoid arthritis (RA) includes erosions and joint space narrowing (JSN). Different mechanisms may underlie their development. The objective of this study was to evaluate predictors of these entities separately. METHODS: Consecutive early RA patients (symptom duration ≤12 months) from a defined area (Malmö, Sweden) recruited during 1995–2005 were investigated. Radiographs of hands and feet were scored by a trained reader according to the modified Sharp-van der Heijde score. Fat mass and lean mass distribution were measured at baseline using dual energy x-ray absorptiometry. Potential predictors of erosion and JSN progression from inclusion to the 5-year follow-up were evaluated. RESULTS: Two hundred and thirty-three patients were included. Radiographs at baseline and 5 years were available for 162 patients. The median (interquartile) progression of erosion and JSN scores were 4 (0–8) and 8 (1–16), respectively. Rheumatoid factor (RF) was a robust significant predictor of both erosion and JSN score progression. In adjusted analyses, anti-CCP antibodies predicted erosions while the erythrocyte sedimentation rate was predictive of both outcomes. Smoking and high baseline disease activity (DAS28 > 5.1) predicted progression of erosions. Baseline erosion score was associated with progression of both erosion and JSN progression, while baseline JSN score was predictive only of the progression of JSN. Overweight/obesity (BMI ≥ 25 kg/m(2)) was a significant negative predictor of JSN score progression (β = − 0.14, p = 0.018, adjusted for RF, age, baseline JSN score) also when additionally adjusting for ever smoking (p = 0.041). Among female patients, this effect was observed in those of estimated post-menopausal age (> 51 years), but not in younger women. The truncal to peripheral fat ratio was associated with less JSN score progression in women, but not in men. CONCLUSIONS: Overweight RA patients had less JSN progression, independent of smoking status. This effect was seen in particular among older women (mainly post-menopausal), but not younger. Truncal fat was associated with less JSN progression in female patients. Smoking predicted erosion progression, and erosions may precede JSN. BMI and fat distribution may influence cartilage damage in early RA and might be related to hormonal factors.